A Modified TAM for Gen Z Investors: Integrating Financial Literacy as a Mediator - Winata, Debora Gracilia; Dewi, Yuli Kartika (Universitas Islam Kadiri, 2026)
This study investigates the determinants affecting the adoption of the Ajaib investment application among Generation Z in Java, employing an adapted Technology Acceptance Model (TAM) that incorporates financial literacy as a mediating variable. The research employs a quantitative methodology with purposive sample of 138 active users and analyzes the data using Partial Least Squares (PLS), revealing that Perceived Ease of Use and Perceived Usefulness significantly improve Financial Literacy. Moreover, Financial Literacy significantly influences both Attitude Toward Using and Behavioral Intention to Utilize the application. The research confirms the mediation function of Financial Literacy, connecting technical variables with user attitudes and intents. The results support the improvement of the TAM model by emphasizing the significance of financial literacy in the adoption of digital investing platforms. It underscores the necessity for application developers and policymakers to enhance usability and financial literacy to boost user engagement, pinpointing Perceived Usefulness, Perceived Ease of Use, and Financial Literacy as critical factors influencing Generation Z's adoption of digital investment tools.